Occupational Therapy Practice in Sleep Management: A Review of Conceptual Models and Research Evidence - Eris C. M. Ho; Andrew M. H. Siu (Occupational Therapy International)
The effectiveness of sleep intervention developed by occupational therapists was reviewed, and a conceptual framework for organizing the developing practice of sleep management in occupational therapy was proposed in this paper. Evidence-based articles on sleep management practice in occupational therapy from 2007 to 2017 were retrieved. Four types of effective sleep management intervention were identified from the literature, including the use of assistive devices/equipment, activities, cognitive behavioral therapy for insomnia, and lifestyle intervention, and the use of assistive device was the most popular intervention. Applying the Person-Environment-Occupation Performance (PEOP) framework, we developed a conceptual framework for organizing occupational therapy practice in sleep management. The future development of occupation-based sleep intervention could focus on strategies to (1) minimize the influence of bodily function on sleep, (2) promote environment conducive to sleep, and (3) restructure daytime activity with a focus on occupational balance.